(untitled) (Communications in Mathematical Research, 2021)
In this paper, we consider the equivalent conditions with L^p-version (1 < p < ∞) of the J.L. Lions lemma. As applications, we first derive the existence of a weak solution to the Maxwell-Stokes type problem and then we consider the Korn inequality. Furthermore, we consider the relation to other fundamental results.